2021
DOI: 10.1016/j.cities.2020.103010
|View full text |Cite
|
Sign up to set email alerts
|

Spread of COVID-19 in China: analysis from a city-based epidemic and mobility model

Abstract: Understanding the processes and mechanisms of the spatial spread of epidemics is essential for making reasonable judgments on the development trends of epidemics and for adopting effective containment measures. Using multi-agent technology and big data on population migration, this paper constructed a city-based epidemic and mobility model (CEMM) to stimulate the spatiotemporal of COVID-19. Compared with traditional models, this model is characterized by an urban network perspective and emphasizes the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 34 publications
2
68
0
Order By: Relevance
“…In order to explore the causes of COVID-19 transmission, we used an OLS regression model. The findings from this analysis showed that population migration in and out of Wuhan was a primary factor in transmission, which is consistent with much of the literature [18,25,35]. The close relationship between population movements and the prevalence of epidemics has long been established [36].…”
Section: Factors Influencing Epidemic Transmissionsupporting
confidence: 86%
See 1 more Smart Citation
“…In order to explore the causes of COVID-19 transmission, we used an OLS regression model. The findings from this analysis showed that population migration in and out of Wuhan was a primary factor in transmission, which is consistent with much of the literature [18,25,35]. The close relationship between population movements and the prevalence of epidemics has long been established [36].…”
Section: Factors Influencing Epidemic Transmissionsupporting
confidence: 86%
“…Aside from migration, only the GDP had a significant impact on COVID-19's spread; that is, in the case of fixed migration in Wuhan, regions with higher GDPs were likely to face more serious epidemic transmission. Currently, only a few studies have focused on the role of economic factors in epidemic transmission [30][31][32][33][34][35][36][37][38][39][40][41][42]. We considered that a higher GDP was suggestive of greater human activity, closer traffic flows, and socioeconomic connections with other cities, as well as higher population movement (both between and within cities).…”
Section: Factors Influencing Epidemic Transmissionmentioning
confidence: 99%
“…Linking transportation networks with epidemic control has become a research focus that has received more and more attention from scholars and practitioners in recent years. For the COVID-19 pandemic most studies, so far, have investigated the risk of COVID-19 infection from Wuhan to other domestic regions ( Zhao et al, 2020 ; Zhang et al, 2020b ; Wei et al, 2021 ) or from one country to other countries via civil aviation ( Christidis and Christodoulou, 2020 ). Some researchers have found that there is a strong correlation between the cumulative number of confirmed cases of COVID-19 and travel by train in China, while travel by car and flight is not significantly correlated with the cumulative number ( Zhao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… Zhang et al (2020) suggested that air and high-speed train (HST) services have played an important role in the spread of COVID-19 across Chinese cities. In China, locking down cities and travel restrictions were major control measures used to stop population migration and slow down the spread of the COVID-19 pandemic ( Wei et al, 2021 ). Therefore, Chinese airlines and China Railway cancelled many flights and HSTs due to greatly reduced intercity traffic demand and travel restrictions announced by the government.…”
Section: Introductionmentioning
confidence: 99%